How Cation Substitutions Affect the Oxygen Reduction Reaction on La2−xSrxNi1−yFeyO4. Issue 9 (2nd March 2022) - Whittingham, Alexander W. H.; Liu, Xinran; Smith, Rodney D. L.
Abstract: The atomic proximity of two disparate structural motifs in interleaved structures such as that adopted by La2 NiO4, which alternates rock salt and perovskite motifs, offers potential synergistic effects and increased tunability for electrocatalyst behavior. Structural and voltammetric analysis of the intersecting composition series LaSrNi1−y Fey O4+δ and La2−x Srx Ni0.7 Fe0.3 O4+δ show that tuning different cation sites uniquely affects structure and behavior. Correlations between X‐ray diffraction and Raman spectroscopy results reveal that structural changes in the a‐b plane are uniformly matched by the c ‐axis following La−Sr exchange, while Ni−Fe exchange distorts the structure by expanding the crystal c‐axis and generating oxygen defects with a distinct signature in Raman spectra. Correlations between rotating ring‐disk electrode voltammetry results and structural parameters show that only Fe substitution has a direct effect on the electrocatalytic oxygen reduction reaction. We link systematic changes observed for onset of electrocatalytic oxygen reduction reaction, Tafel slope, and selectivity to distortions in the B‐site environments. This analysis demonstrates that correlational analysis linking electrochemical behavior parameters to multiple structural characterization techniques is an effective means to probe the effect of individual compositional substitution on electrocatalytic behavior. Abstract : Variations of structural parameters measured using Raman spectroscopy and X‐ray diffraction enable structure‐property analysis on the effect of compositional tuning on electrocatalytic behavior of La2−x Srx Ni1−y Fey O4+δ . Analysis of correlations reveals that B‐site substitution yields a structural distortion that alters product selectivity for the oxygen reduction reaction.